1998
DOI: 10.1177/0743554898131003
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Humor and Depression in Adolescent Psychiatric Inpatients and High School Students

Abstract: Humor may be an important coping skillfor dealing with emotional difficulties during adolescence. The relations between humor and symptoms of depression in high school students and in depressed adolescent psychiatric inpatients were examined in the present study. Assessment of humor included measures of humor appreciation, humor creativity, and humor coping. Professional comedians rated humor creativity. Depression was assessed with self-report measures of depressed mood, self-esteem, and hopelessness. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…In particular, affiliative and self-enhancing humor were negatively correlated with depressive symptoms and positively correlated with personal adjustment, while self-defeating and aggressive humor evidenced the opposite pattern. These findings are congruent with the adolescent literature [33,44,48]. Seven of the eight contrasts between Martin et al [9] adult sample and the adolescent sample correlations with different but convergent measures were not significant, suggesting that the nature of responses to the humor scales and the relationship of these responses to measures of depressive symptoms and well-being were relatively similar for adults and adolescents.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In particular, affiliative and self-enhancing humor were negatively correlated with depressive symptoms and positively correlated with personal adjustment, while self-defeating and aggressive humor evidenced the opposite pattern. These findings are congruent with the adolescent literature [33,44,48]. Seven of the eight contrasts between Martin et al [9] adult sample and the adolescent sample correlations with different but convergent measures were not significant, suggesting that the nature of responses to the humor scales and the relationship of these responses to measures of depressive symptoms and well-being were relatively similar for adults and adolescents.…”
Section: Discussionsupporting
confidence: 89%
“…To the extent that humor is conceptualized as a form of coping or defense, one would expect positive humor to be associated with adjustment and negative humor to be associated with poor adjustment, including depressive symptoms. Toward that end, Freiheit et al [44] found that when both depressed and non-depressed adolescents used humor to deal with stressful situations they reported significantly lower levels of depressive symptoms. Furthermore, in studies of humor as a coping strategy with adults, humor coping has been associated with lower levels of depressive symptoms [32,39,[45][46][47].…”
Section: Humor and Depressive Symptomsmentioning
confidence: 98%
“…Results of these are often contradictory and do not allow a general conclusion about the proverb "laughter each day keeps the doctor at bay". A sample of juvenile patients showed predominantly negative correlations of humor interventions and depressive symptoms (Freiheit et al, 1998). Humor might be an option to learn how to deal with physical and psychological symptoms without feeling embarrassed (Raewel, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kuiper et al (1995) have demonstrated that higher levels of coping humor were associated with more positive cognitive appraisals, higher motivation levels, and greater positive affect for completing a task. Other studies have also demonstrated facilitative effects, with a greater sense of humor related to a more positive self-concept, increased self-esteem, higher sociability levels, and decreased levels of depression and hopelessness (Freiheit et al 1998;Kuiper and Martin 1993;Kuiper et al 1992;.…”
mentioning
confidence: 93%